2017
DOI: 10.1186/s13063-017-1985-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic effects of aerobic exercise on blood pressure in resistant hypertension: study protocol for a randomized controlled trial

Abstract: BackgroundResistant hypertension is a specific condition that affects approximately 10% of subjects with hypertension, and is characterized by persistently high blood pressure levels even using therapy of three or more antihypertensive agents or with blood pressure control using therapy with four or more antihypertensive agents. Changes in lifestyle, such as physical exercise, are indicated for controlling blood pressure. However, investigating studies about this therapy in individuals with resistant hypertens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 53 publications
3
6
0
1
Order By: Relevance
“…They found that a single session of aerobic exercises significantly decreased ambulatory BP. Nascimento et al [105] studied the acute and chronic effects of aerobic exercises on BP in subjects with resistant hypertension. They found that 8weeks of mild aerobic exercises significantly reduced BP.…”
Section: The Effects Of Increasing the Aerobic Capacity As A Protectimentioning
confidence: 99%
“…They found that a single session of aerobic exercises significantly decreased ambulatory BP. Nascimento et al [105] studied the acute and chronic effects of aerobic exercises on BP in subjects with resistant hypertension. They found that 8weeks of mild aerobic exercises significantly reduced BP.…”
Section: The Effects Of Increasing the Aerobic Capacity As A Protectimentioning
confidence: 99%
“…Recently, exercise training (ExT) has been reported to be beneficial to patients suffering from hypertension when used as a supplement to pharmaceutical antihypertensive therapies (Nogueira-Ferreira et al, 2016). Research in athletes (Caselli et al, 2017), patients (Nascimento et al, 2017; Liu et al, 2018) and animals (Masson et al, 2015b; Rocha et al, 2016) also suggests that it’s beneficial in the treatment of hypertension. ExT can effectively down-regulate the PICs in the PVN, enhance the baroreflex sensitivity and lower blood pressure in hypertensive rats (Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that ExT effectively lowers BP, decreases cardiac output, and enhances the baroreflex sensitivity in patients [8] and animals [6,9,10] with hypertension. However, the exact mechanisms of exerciseinduced effects in hypertension are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%